Electro-emissive device based on novel PANI/Au composite films with neoteric mosaic structure for infrared stealth and thermal radiation control. (10th September 2021) - Wang, Bo; Xu, Gaoping; Song, Shanshan; Ren, Zichen; Li, Xiaobai; Li, Jingjing; Xu, Xiaoqian; Zhou, Wei; Li, Hongbin; Zhang, Leipeng; Li, Yao
Highlights: Novel composite films based on PANI and Au particles were prepared successfully. The novel composite films have neoteric mosaic structure. Good IR emissivity tunability was obtained by the novel composite film. The EEDs based on the composite films showed good IR stealth capability. The EEDs showed promising applications in thermal radiation control. Abstract: Infrared (IR) stealthy material is mainly to reduce or change the IR radiation characteristics of the target, reduce the probability of the target being detected, however, its application is limited by the ability to control the emitted thermal radiation from the material surface. This study demonstrates a novel PANI/Au composite film designed with neoteric mosaic structure prepared by the galvanostatic method which has an enormous IR radiation regulation range and good thermal radiation control ability. The results show that PANI/Au composite film exhibits supereminent IR emissivity modulation capability. At 13 μm, the variation of infrared emissivity (△ε) of leucoemeraldine base (LB) state and emeraldine salt (ES) state can up to 0.552. In the wavelength range of 8–14 μm and 2.5–25 μm, the emissivity of the composite film changes by 0.491 and 0.403, respectively. Electro-emissive devices (EEDs) based on PANI/Au composite films show excellent infrared stealth and thermal radiation control effects. The maximum adjustable temperature between the device and the environment can up to 4.8 °C. The research results provide a basis for the selection of thermal radiation control materials combining infrared stealth and radiation information management. Graphic abstract: Image, graphical abstract